Integration of Anti-Corruption Education (PAK) In Islamic Religious Education (PAI) With Neuroscience Approach (Multi-Case Study in Brain Friendly PAUD: I Sleman Kindergarten Yogyakarta) - Suyadi Suyadi (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
Islamic Religious Education (PAI) is not sufficient for cultivating anti-corruption character. As a result, future generations at risk of experiencing brain disorders which are considered normal but unhealthy. This study aims to integrate PAI and Anti-Corruption Education (PAK) with neuroscience approach in PAUD. This research used a qualitative approach in the form of field research in brain-friendly PAUD, i.e.1 Sleman Kindergarten Yogyakarta. Data collection technique was done by observation, interview, and documentation. Data analysis was done in descriptive, interpretative, and comparative. The research indicates that the application of PAK in I Sleman Kindergarten is by following findings National Learning Movement of I'm an Honest Kid (Gernas Manjur), while PAI is implemented thematically and scientifically, but it is not yet integrated. This research integrates PAK and PAI by extending the forms of corruption into Gernas Manjur and deepening the themes of PAI learning based on neuroscience learning theory.